Framing of Hamas Attacks on Israel in Al-Jazeera and BBCCoverage - Zawawi, Moh; Jambak, Mellinda Raswari; Hasanah, Ummi; Basid, Abdul; Anas, Khoirul (Makassar State University, 2024)
Abstract. Digital media provides the latest news on global issues, particularly in the realm of religion, attracting a broad audience. This research explores how international mass media outlets Al-Jazeera and BBC frame their coverage of Hamas' attack on Israel on October 7. Utilizing a qualitative descriptive research method, the study aims to comprehensively depict the framing processes employed by Al-Jazeera and BBC in reporting on the Hamas-Israel conflict. Primary data includes Al-Jazeera's article